2015
DOI: 10.18488/journal.1/2015.5.12/1.12.740.754
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Influencing the Implementation of Enterprise Risk Management in the Nigerian Banking Sector

Abstract: Enterprise risk management (ERM) is an organized, dependable and reproducible process across the entire system for identifying, measuring, controlling and reporting of opportunities and threats that could impact on the objectives of the organization. The purpose of this study is to empirically examine the extent of ERM implementation in the Nigerian banking sector and the identification of antecedents influencing the adoption. 722 questionnaires were administered to top, middle and lower level managers across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Not only is ERM believed to have enhanced firm's ability to prevent the impact of economic crisis, it is believed that it will bring about an improved value relevance of accounting information for firms practising ERM (COSO, 2004). The support for ERM in most countries of the world today is a salient success in mitigation of further economic crisis and improvement in the quality of accounting information (Dabari & Saidin, 2015). In Nigeria, the research on ERM has gained prominence due to corporate scandals (Cadbury Nigeria in 2006; Banking crisis in 2009) experienced in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…Not only is ERM believed to have enhanced firm's ability to prevent the impact of economic crisis, it is believed that it will bring about an improved value relevance of accounting information for firms practising ERM (COSO, 2004). The support for ERM in most countries of the world today is a salient success in mitigation of further economic crisis and improvement in the quality of accounting information (Dabari & Saidin, 2015). In Nigeria, the research on ERM has gained prominence due to corporate scandals (Cadbury Nigeria in 2006; Banking crisis in 2009) experienced in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, (COSO, 2004) emphasized that the implementation of ERM by companies largely depend on corporate governance, enabling laws, regulations, and listing standards. Therefore, the implementation of ERM framework is usually effected by existence of audit committee, risk management committee, chief legal officer, chief risk officer, regulations like, laws and other regulatory compliance and the size of the firm (Ishaya & Siti, 2015).…”
Section: The Concept Of Risk and Enterprise Risk Management (Erm)mentioning
confidence: 99%
“…In addition, Committee of Sponsoring Organizations of the Treadway Commission (COSO, 2004) emphasized that implementation of ERM by companies largely depend on corporate governance, enabling laws, regulations, and listing requirements. According to Ishaya and Siti (2015), the implementation of ERM is usually influenced by existence of corporate internal audit effectiveness, existence of risk management committee, existence of chief legal officer, chief risk officer, firm size and regulatory support like, laws and other regulatory compliance.…”
mentioning
confidence: 99%
“…For instance, Nahar et al (2016) report that there is significant relationship between risk disclosure, existence of risk management committee, and number of risk committees and performance of banks in Australia. Likewise, with the use of primary data collected from 722 managers of 21 banks and their branches in Nigeria, Dabari and Saidin (2015) found that enterprise risk management (ERM) is implemented by some banks in Nigeria, but yet to be implement by others. As a result, this study suggests the following hypothesis:…”
Section: Risk Management Disclosure and Firm Performancementioning
confidence: 99%